2011
DOI: 10.1007/s11892-011-0237-4
|View full text |Cite
|
Sign up to set email alerts
|

Flavor Learning In Utero and Its Implications for Future Obesity and Diabetes

Abstract: The concept of prenatal flavor learning can be used to motivate women to eat healthy foods. The flavors of the foods in the maternal diet are found in the amniotic fluid swallowed by the fetus, with the fetus developing a preference for those flavors that is shown to persist in infancy. Furthermore, flavor preferences in infancy can persist into childhood and even into adulthood. Thus, the intrauterine environment may have a life-long influence on flavor preferences and healthy eating. This is an empowering co… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
6
0
2

Year Published

2014
2014
2022
2022

Publication Types

Select...
4
4
1

Relationship

0
9

Authors

Journals

citations
Cited by 19 publications
(10 citation statements)
references
References 28 publications
1
6
0
2
Order By: Relevance
“…The current literature is already quite consistent about the transmission of the olfactory and taste characteristics of the mater- nal diet via amniotic fl uid -from the second quarter, when foetal gustatory and olfactory gestational receptors develop -and breast milk 35 . Several studies have shown that regular and frequent exposure of the mother to FV favours faster acceptance of these foods during the supplementary feeding of children and reduces the frequency and severity of feeding diffi culties up to the age of seven years 35,36,37 . It has already been demonstrated that consumption and ex-posure to FV in this phase can have an effect on epigenetic aspects related to smell and taste, including perceptions of bitter/sweet/umami fl avour and, in the future, infl uencing their food preferences 35,38 .…”
Section: Cyclical Infl Uences On Consumptionmentioning
confidence: 99%
“…The current literature is already quite consistent about the transmission of the olfactory and taste characteristics of the mater- nal diet via amniotic fl uid -from the second quarter, when foetal gustatory and olfactory gestational receptors develop -and breast milk 35 . Several studies have shown that regular and frequent exposure of the mother to FV favours faster acceptance of these foods during the supplementary feeding of children and reduces the frequency and severity of feeding diffi culties up to the age of seven years 35,36,37 . It has already been demonstrated that consumption and ex-posure to FV in this phase can have an effect on epigenetic aspects related to smell and taste, including perceptions of bitter/sweet/umami fl avour and, in the future, infl uencing their food preferences 35,38 .…”
Section: Cyclical Infl Uences On Consumptionmentioning
confidence: 99%
“…Regular pre-exposure to anise flavor through mothers’ diet has shown to be effective in inducing a preference for anise odor in newborn babies (Schaal et al, 2000). Some preferences are innate in nature, for example bitterness aversion or sweetness preference (Mennella et al, 2005; though see Desor et al, 1975), nevertheless prenatal life has been shown to have an impact also on later food preferences, showing the importance of mothers’ diet quality during gestation (Trout and Wetzel-Effinger, 2012). …”
Section: The Mediation Of Exposurementioning
confidence: 99%
“…Therefore, the higher preference for and acceptance of sour taste could also foster higher intake of acidic foods and thereby improve the ability to perceive sour taste. As taste preferences are often determined early in life, 5 and given that multiple factors influence individual food intake differently, 34 it may be very difficult to verify such a hypothesis. Liem et al 35 assessed the preferences of mothers and their children and found that children with a higher sour tolerance were less food neophobic and ate more different fruits, which could also be for a factor of successful weight maintenance.…”
Section: Discussionmentioning
confidence: 99%